Emotional Representation in Divorce Conflict in the Film “Marriage Story” - Bayu Setiawan; Pungky Arifianto; Awanda Aura Putri Alievia (Gorga : Jurnal Seni Rupa, 2026)
This film explores the intricacies of a marriage that faces challenges due to ineffective communication and the accumulation of suppressed emotions between the characters, Charlie Barber and Nicole Barber. This study seeks to analyze the portrayal of emotions in divorce conflicts depicted in Noah Baumbach’s film, Marriage Story. The research employs a descriptive qualitative method utilizing Roland Barthes’ semiotic approach, which focuses on the analysis of denotative, connotative, and mythological meanings within visual and narrative signs. Data collection was conducted through the observation of several pivotal scenes that illustrate the emotional evolution of the characters, encompassing the initial phase of relationship warmth, the emergence of conflict, the culmination of arguments, and the stage of acceptance. Data analysis in this study was conducted through a multi-step process, including sign identification, denotative analysis, connotative analysis, and myth analysis. The research findings reveal that the representation of emotions in film is conveyed not solely through dialogue but also through visual signs such as facial expressions, body movements, spatial composition, and character interactions. These signs generate connotative meanings that encapsulate the complexity of emotions in divorce, including a sense of loss, anger, regret, and lingering affection. Furthermore, films depict divorce as an emotional process that is not linear but dynamic and ambivalent, wherein both characters experience internal conflict. This study is anticipated to contribute to the field of visual communication studies, particularly in comprehending the representation of emotions within film.